2000
DOI: 10.1044/jslhr.4302.293
|View full text |Cite
|
Sign up to set email alerts
|

Verbal Working Memory and Sentence Comprehension in Children With Specific Language Impairment

Abstract: In this study we examined the influence of verbal working memory on sentence comprehension in children with SLI. Twelve children with SLI, 12 normally developing children matched for age (CA), and 12 children matched for receptive vocabulary (VM) completed two tasks. In the verbal working memory task, children recalled as many real words as possible under three processing load conditions (i.e., no-load condition; single-load condition, where words were recalled according to physical size of word referents; and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
200
1
22

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(238 citation statements)
references
References 28 publications
15
200
1
22
Order By: Relevance
“…Hypothesis 1 predicted that children with SLI show decrements in listening span compared to their age-matched and language-matched peers. The listening span measures served to ensure that the SLI participants in this study show similar performance patterns to other reported data (e.g., Ellis-Weismer, Evans, & Hesketh, 1999, Marton & Schwartz, 2003Montgomery, 1995Montgomery, , 2000. The results of the listening span task are in line with previous findings.…”
Section: Discussionsupporting
confidence: 80%
“…Hypothesis 1 predicted that children with SLI show decrements in listening span compared to their age-matched and language-matched peers. The listening span measures served to ensure that the SLI participants in this study show similar performance patterns to other reported data (e.g., Ellis-Weismer, Evans, & Hesketh, 1999, Marton & Schwartz, 2003Montgomery, 1995Montgomery, , 2000. The results of the listening span task are in line with previous findings.…”
Section: Discussionsupporting
confidence: 80%
“…The other half were asked to remember digits while processing the sentences. Specifically, before each sentence they were presented with an orienting asterisk for 500 msec, followed by a random seven-digit string for language impairment are known to have working memory and/or phonological deficits; similar deficits are exhibited by second-language learners in their second language (Bird et al, 2003;McDonald, 2006;Montgomery, 2000aMontgomery, , 2000b. These processing deficits could contribute to poor plural or agreement performance, whereas SVO word order is relatively well maintained.…”
Section: Methodsmentioning
confidence: 99%
“…Working memory capacity was measured using a syntax-free size judgment task (Cherry & Park, 1993;Montgomery, 2000aMontgomery, , 2000b, in which participants were given a list of items that they were to give back in the order of physically smallest to physically largest object. For example, if given pig, door, butterfly, participants were to say, "butterfly, pig, door."…”
Section: Stimulimentioning
confidence: 99%
“…Limitações em sua capacidade podem resultar em dificuldades para leitura (Gathercole, Alloway, Willis, & Adams, 2006;Gathercole, Lamont, & Alloway, 2006;Siegel & Ryan, 1989;Swanson, 2003), matemática (Bull & Scerif, 2001;Geary, Hoard, Byrd Craven, & DeSoto, 2004;Gersten, Jordan, & Flojo, 2005), linguagem (Archibald & Gathercole, 2006;Ellis Weismer et al, 2000;Montgomery, 2000), e atenção (Barkley, 1997;Martinussen & Tannock, 2006). Portanto, a avaliação dos componentes da memória operacional pode fornecer entendimentos cruciais sobre transtornos de aprendizagem (Gathercole & Alloway, 2004).…”
unclassified